Theoretical and Experimental Investigations of Laser Annealing Non-Stoichiometric SiOx Films - Gavryliuk, O.O.; Semchuk, O.Yu.; Lytovchenko, B.V. (Physics and Chemistry of Solid State, 2015)
In this work, spreading of temperature profiles and influence of a temperature on forming silicon nanoparticles in non-stoichiometric SiOx films after laser annealing is investigated. Using parabolic thermal conductivity equation, mathematical simulation of temperature profiles is realized in a non-stoichiometric SiOx film after laser annealing. It is shown that temperature 1800 K on a SiOx surface is sufficient for separating the film material on silicon dioxide and its nanoparticles. IR-investigations confirm this separating.